Adipokinetic hormone activities in insect body infected by entomopathogenic nematode - Ibrahim, Emad; Hejníková, Markéta; Shaik, Haq Abdul; Doležel, David; Kodrík, Dalibor (Journal of insect physiology, 2017)
The role of adipokinetic hormone (AKH) in the firebug Pyrrhocoris apterus adults infected by the entomopathogenic nematode (EPN) Steinernema carpocapsae was examined in this study. It was found that co-application of EPN and AKH enhanced firebug mortality about 2.5 times within 24h (from 20 to 51% in EPN vs. EPN+AKH treatments), and resulted in metabolism intensification, as carbon dioxide production in firebugs increased about 2.1 and 1.6times compared to control- and EPN-treated insects, respectively. Accordingly, firebugs with reduced expression of AKH receptors showed a significantly lower mortality (by 1.6 to 2.9-folds), and lower general metabolism after EPN+AKH treatments. In addition, EPN application increased Akh gene expression in the corpora cardiaca (1.6times), AKH level in the corpora cardiaca (1.3times) and haemolymph (1.7times), and lipid and carbohydrate amounts in the haemolymph. Thus, the outcomes of the present study demonstrate involvement of AKH into the anti-stress reaction elicited by the nematobacterial infection. The exact mechanism by which AKH acts is unknown, but results suggested that the increase of metabolism and nutrient amounts in haemolymph might play a role.
Keywords: Male; Hemolymph; Pyrrolidonecarboxylic Acid; Insect Hormones; Pyrrhocoris apterus; hemolymfa; orgánová specificita; Corpora Allata; corpora allata; Animals; Oligopeptides; RNAi; mužské pohlaví; Metabolism; hmyzí hormony; kyselina pyrrolidonkarboxylová; Rhabditida; Mortality; AKH receptor; Heteroptera; zvířata; Organ Specificity; Akh gene expression; oligopeptidy